Design and Analysis of Delimiters for Selection-Action Pen Gesture Phrases in Scriboli - Hinckley, Ken; Baudisch, Patrick; Ramos, Gonzalo; Guimbretiere, Francois (CHI '05 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2005)
We present a quantitative analysis of delimiters for pen gestures. A delimiter is “something different” in the input stream that a computer can use to determine the structure of input phrases. We study four techniques for delimiting a selection-action gesture phrase consisting of lasso selection plus marking-menu-based command activation. Pigtail is a new technique that uses a small loop to delimit lasso selection from marking. Handle adds a box to the end of the lasso, from which the user makes a second stroke for marking. Timeout uses dwelling with the pen to delimit the lasso from the mark. Button uses a button press to signal when to delimit the gesture. We describe the role of delimiters in our Scriboli pen interaction testbed, and show how Pigtail supports scope selection, command activation, and direct manipulation all in a single fluid pen gesture.